Inter-Party Defection: Does Tanzania Need Anti-Defection Law? - Renatus Bujiku, Robert; Abdallah Saidi, Mpawenimana; Ilan Mersat, Neilson; Puyok, Arnold (International Journal of Psychosocial Rehabilitation, 2020)
In spite of a manifest increase in the number of legislative representatives who defect from one party to the other in Tanzania, there has been scanty literature to understand why this massive defection is taking place now. This research article embarked to fill this gap of knowledge. The authors presented empirical findings obtained in a Tanzanian political context whereby defectors were purposively sampled for in-depth understanding of a phenomenon. A total of thirty (30) key informants from different registered political parties were prudently chosen to participate in the study. The results of this research revealed that there are various political reasons that influence interparty defection amongst politicians in Tanzania; these include personal interests, intra-party conflict, national interests, and ethnic group interests. Thus, the study recommends to policymakers and other political stakeholders to consider adoption of an anti-defection law so that to regulate or control unnecessarily defection done by sitting legislators or representatives. By doing so, it will help to protect unreasonable utilization of national scarce resources for repeatedly by-elections.